(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: Objective of this study is to determine the result of everted end to end urethroplasty in those patients who have traumatic bulbar and membranous urethral stricture. Methods: The conducted place of this study was the department of Urology, Lahore General Hospital, Lahore for a duration of one year from 01-01-2012 to 31-12-2012. The included patients were 30 in number in the study. A single surgical team performed the procedure and Uroflowmetry and subjective evaluation was done on 2nd week, 1st month and 4th month and 12th month post operatively. Results: 24.43±12.39 years were labeled as mean age of patients. The findings of retrograde and Antigrade Urethrogram were that the stricture at bulbo membranous junction was in 2 patients and the blind stricture at bulbar level was in 28 patients. 6.83±4.25 months were the average interval between the initial injury and urethroplasty. Mean length of the stricture was 1.83±0.63 cm after operation. On follow up of 2 weeks after operation, 15 patients were having subjective grading of 1 and 2 respectively (50 % in each). After 1 month of operation, grade 1 was reported in 23 patients (76.67%) and Grade-2 and Grade-3 subjective grading were present in 2 patients (6.67%) in each. 22 patients (73.34%) had 1 Uroflowmetry grading and 8 patients (26.67%) had 2 Uroflowmetry grade after 14 days of operation. After the follow up of 1 month, grade-1 was present in 19 patients (63.34%), Grade 2 was in 6 patients (20%) and Grade-3 Uroflowmetery was present in 2 patients (6.67%). Only 24 patients (80%) had presentation of grade-1 subjective improvement symptom and uroflowmetry at 4th month and 1 year after operation. The recurrence of stricture at follow up of 1 month was in 3 patients (10%) and at follow up of 4 month another 3 patients (10%) developed recurrent stricture in whom Internal Optical Urethrotomy (IOU) was subjected. Among the 6 patients (20%) of stricture recurrence, single IOU was enough for 2 patients (6.67%), 3 patients (10%) improved with 2 times IOU having 3 months interval and perineal urethroplasty was ultimately performed in 1 patient (3.34%) after repeated IOU. Failure was considered if IOU was repeated along with other intervention. Conclusion: The treatment of choice for short traumatic bulbar and membranous urethral strictures is everted end-to-end urethroplasty having approximate 100% cure rates with minimum complications.